Cold atmospheric plasma jet as a possible adjuvant therapy for periodontal disease - Koga-ito, Cristiane Yumi [UNESP]; Lima, Gabriela de Morais Gouvêa [UNESP]; Borges, Aline Chiodi [UNESP]; Nishime, Thalita Mayumi Castaldelli; Santana-Melo, Gabriela de Fatima [UNESP]; Kostov, Konstantin Georgiev; Mayer, Marcia Pinto Alves (MDPI, 2021)
: Due to the limitations of traditional periodontal therapies, and reported cold atmospheric plasma anti-inflammatory/antimicrobial activities, plasma could be an adjuvant therapy to periodontitis. Porphyromonas gingivalis was grown in blood agar. Standardized suspensions were plated on blood agar and plasma-treated for planktonic growth. For biofilm, dual-species Streptococcus gordonii + P. gingivalis biofilm grew for 48 h and then was plasma-treated. XTT assay and CFU counting were performed. Cytotoxicity was accessed immediately or after 24 h. Plasma was applied for 1, 3, 5 or 7 min. In vivo: Thirty C57BI/6 mice were subject to experimental periodontitis for 11 days. Immediately after ligature removal, animals were plasma-treated for 5 min once—Group P1 (n = 10); twice (Day 11 and 13)—Group P2 (n = 10); or not treated—Group S (n = 10). Mice were euthanized on day 15. Histological and microtomography analyses were performed. Significance level was 5%. Halo diameter increased proportionally to time of exposure contrary to CFU/mL counting. Mean/SD of fibroblasts viability did not vary among the groups. Plasma was able to inhibit P. gingivalis in planktonic culture and biofilm in a cell-safe manner. Moreover, plasma treatment in vivo, for 5 min, tends to improve periodontal tissue recovery, proportionally to the number of plasma applications.
Keywords: Biocompatibility; Cold plasma; Disinfection; Periodontitis; Porphyromonas gingivalis